Unveiling the non-linear dynamics: quantile regression of financial development's impact on environmental degradation in BRICS and G7 nations - Fortune Ganda; Cristina Ruza (Discover Sustainability)
Abstract The growing environmental risks have become a major concern these days. This study examines within the EKC framework the long-term impact of income and financial development on environmental degradation assuming that this relationship is non permanent. The non-linear effect of financial development on CO2 and GHGs has not been analyzed in the literature, and this study applies panel quantile regressions to the group of BRICS and G7 over 1990–2019. It also separately assesses the long term impact of financial institutions versus financial markets development. The results confirm that financial development helps reducing CO2 and GHGs emissions after a threshold within the group of lower emitters (inverted U-shaped pattern). Going further, financial institutions have a positive effect on the environment, but financial markets exert a negative impact. The EKC hypothesis does not find support in this study and there is a U-shaped link between growth and polluting emissions. These empirical findings contribute to a better understanding of the pollution-income-financial development nexus in the long-term and provide insight to the policymakers, regulatory bodies, financial intermediaries and investors aligned with sustainable development goals. Graphical Abstract